2017
DOI: 10.3171/2017.2.focus1731
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion of tandem cerebral aneurysms: a multi-institutional retrospective study

Abstract: OBJECTIVEFlow diversion has proven to be an efficacious means of treating cerebral aneurysms that are refractory to other therapeutic means. Patients with tandem aneurysms treated with flow diversion have been included in larger, previously reported series; however, there are no dedicated reports on using this technique during a single session to treat this unique subset of patients. Therefore, the authors analyzed the outcomes of patients who had undergone single-ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(17 reference statements)
1
11
0
2
Order By: Relevance
“…The complete occlusion rate in the coiling group was 77.4%, which is consistent with the current literature regarding both TAs [10,11] and single wide-necked IAs [14,15]. In the FDS treatment, the complete occlusion rate was reported to range from 85 to 90% in previous studies [6][7][8][9]. In our cohort, only 58.8% of the IAs achieved complete occlusion in the FDS group.…”
Section: Coiling Treatment and Fds Treatmentsupporting
confidence: 91%
See 2 more Smart Citations
“…The complete occlusion rate in the coiling group was 77.4%, which is consistent with the current literature regarding both TAs [10,11] and single wide-necked IAs [14,15]. In the FDS treatment, the complete occlusion rate was reported to range from 85 to 90% in previous studies [6][7][8][9]. In our cohort, only 58.8% of the IAs achieved complete occlusion in the FDS group.…”
Section: Coiling Treatment and Fds Treatmentsupporting
confidence: 91%
“…At the latest follow-up, 76.5% IAs achieved complete occlusion, and all patients had mRS scores of 0-1. At the same time, many studies have reported the safety and efficacy of FDS in management of tandem lesions [6][7][8][9]. However, there is still a debate over which treatment is better, and studies comparing the 2 strategies are still rare.…”
Section: Coiling Treatment and Fds Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Awad et al [27] reported PED treatment for tandem aneurysms in seventeen patients with a mean final Raymond-Roy score of 1.3±0.7. We had one unruptured, previously untreated M1 aneurysm that was found during the work-up of tinnitus in a 64-year-old female patient.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, flow diversion was used to treat complex, giant and fusiform aneurysms. However, with more data available which supports the efficacy and safety of flow diverters for treatment of smaller (<7 mm) aneurysms, [21][22][23] the device is now being used more often in patients with small and less complex aneurysms. Given that the average size of a ruptured aneurysm was determined to lie between 6 mm and 7 mm, 24 it is important to consider treatment in patients with aneurysms approaching this size.…”
Section: Discussionmentioning
confidence: 99%